2020
DOI: 10.1101/2020.11.08.373290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resource uptake and the evolution of moderately efficient enzymes

Abstract: Enzymes speed up reactions that would otherwise be too slow to sustain the metabolism of self-replicators. Yet, most enzymes seem only moderately efficient, exhibiting kinetic parameters orders of magnitude lower than their expected physically achievable maxima. Here, we question how these parameters evolve using a mechanistic model where enzyme efficiency is a key component of individual competition for resources. We show that kinetic parameters are under strong directional selection only up to a point, above… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…It was previously suggested that although nearly optimal enzymes exist, most enzymes show moderate catalytic efficiencies and are far from catalytic perfection 32,33 . Most of these studies have focused on “composite” efficiency quantities to study the evolutionary pressure, neglecting the independent effect of each dimension on the evolutionary processes 43,44 . In this study, our analysis was focused and limited to the kinetic design and modes of operations of enzymes at maximal reaction-rates.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously suggested that although nearly optimal enzymes exist, most enzymes show moderate catalytic efficiencies and are far from catalytic perfection 32,33 . Most of these studies have focused on “composite” efficiency quantities to study the evolutionary pressure, neglecting the independent effect of each dimension on the evolutionary processes 43,44 . In this study, our analysis was focused and limited to the kinetic design and modes of operations of enzymes at maximal reaction-rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fitness may depend upon more phenotypes than those being assayed 27 or the relationship between phenotype and fitness may be inherently nonlinear, for example reflecting a tradeoff between the costs and benefits associated with a phenotype 28 . In the latter case, selection may favor a low or intermediate phenotypic value 29,30 ; e.g., an intermediate gene expression level, [31][32][33] , enzyme efficiency 34 or protein production rate or activity 35 . Such non-linearities are a cause of epistasis 16,[36][37][38] , and they can transform the effects of mutations as they map onto phenotype and fitness 37 , thus rendering the topographical properties of a fitness landscape qualitatively different from those of its underlying genotype-phenotype landscape (Fig.…”
Section: Introductionmentioning
confidence: 99%